PERAN PENYULUH PERTANIAN TERHADAP PENINGKATAN PRODUKSI TOMAT (SOLANUM LYCOPERSICUM) DI KELOMPOK TANI SURI PUDI, DESA DONE, KECAMATAN MAGEPANDA - Marietha Gorety, Ersilia; Iawan Saputera Wanda, Taras; Yakob Da Rato, Yoseph (Jurnal Biogenerasi, 2025)
Efforts to increase agricultural production cannot be separated from the role of agricultural instructors. The existence of agricultural extension workers can help farmers obtain the information and technology they need. The high or low productivity of a farming business is influenced by the difficulty of farmers in adopting new technology. This research aims to determine the level of role of agricultural instructors towards tomato farmers and the relationship between the role of agricultural instructors in increasing tomato (Solanum Lycopersicum) production in the Suri Pudi farmer group, Done Village, Magepanda District. The method used in this research is a survey method with a quantitative approach. The sample used was a saturated sample of 32 people, and data analysis used a Likert scale and Spearman rank. The results of the research show that the level of role of agricultural instructors towards tomato farmers in the Suri Pudi farmer group, Done Village, Magepanda District is in the high category with a value of 76.2%. The role of agricultural instructors as motivators, catalysts, communicators, consultants and facilitators does not have a significant relationship, while the role of instructors as educators and organizers has a significant relationship in increasing tomato production. Overall, the role of extension workers does not have a real or significant relationship in increasing tomato production. This shows that the greater the role of extension workers, the greater the increase in tomato production, which is not necessarily true.